An Open-Source Framework For CFD-Based Digital Twins: A Case Study On Storm Water Management - Shahsavari, Sajad; Chaudhari, Ashvinkumar; Immonen, Eero; Haghbayan, Hashem (United Kingdom, 2026)
Digital Twins (DTs) are increasingly applied for optimization of operations in logistics, healthcare, smart cities, and beyond. However, implementing high-fidelity DTs remains challenging in computationally intensive domains such as Computational Fluid Dynamics (CFD). While simplified models can facilitate real-time operation, they often lack physical fidelity. This article presents an open-source scalable software framework along with a case study of CFD-based digital twining on stormwater management.
The presented framework enables online execution of CFD-based models by containerizing and integrating them into OpenShift platform,  providing a two-way communication channel for simulation parameters and results. The framework is capable of dynamically scaling computing resources to run computationally-intensive CFD-models. In the case study, we present a novel CFD simulation model of a bioretention cell intended to reduce runoff volumes of urban stormwater. The simulation model, implemented in OpenFOAM, is then integrated into the presented software framework to create the DT. The framework source code, simulation model and the DT are made publicly available to promote future research.
Proceedings of the 39th ECMS International Conference on Modelling and Simulation ECMS 2025